Kinetic analysis and degradation pathway for m-dichlorobenzene removal by Brevibacillus agri DH-1 and its performance in a biotrickling filter. (May 2017) - Yang, Bai-ren; Sun, Zhu-qiu; Wang, Li-ping; Li, Zhao-xia; Ding, Cheng
Graphical abstract: Highlights: Growth and degradation kinetics for m -dichlorobenzene degradation by a strain DH-1 were studied. A putative pathway for m -dichlorobenzene degradation was presented. m -Dichlorobenzene removal and pressure drop in a biotrickling filter inoculated with strain DH-1 was analyzed. Abstract: A strain, Brevibacillus agri DH-1, isolated from dry lands was used to remove m -dichlorobenzene. After 48 h culturing, the concentrations of m -dichlorobenzene decreased from 26–130 to 7.87–28.87 mg/L and dry cell weight for bacterial growth reached 52.43–75.05 mg/L. The growth and degradation kinetics were analyzed by the fitting of Haldane-Andrews model and pseudo first-order model. A degradation pathway was proposed according to major intermediates (phenol), chloride ion variation, ring-opening enzyme activity, and high mineralization (0.47 gCl- /g m -dichlorobenzene, 0.65 gco2 /g m -dichlorobenzene, 0.15 gDCW /g m -dichlorobenzene ). In addition, the performance in a biotrickling filter (BTF) was evaluated through removal efficiency and pressure drop values with increasing inlet loading rate from 4.10 to 122.57 g/m 3 /h at three empty bed residence time points (30 s, 60 s, and 90 s). The results demonstrated that strain DH-1 possessed high removal efficiency and stable operation in a BTF.